145k views
1 vote
Solve for x.

5 (2 - 2x) = 3x


x = (?)/(?)
Reduce your answer to simplest form.​

Solve for x. 5 (2 - 2x) = 3x x = (?)/(?) Reduce your answer to simplest form.​-example-1

2 Answers

1 vote

Answer:

The value of x is 10/13.

Explanation:

First step, you have to expand the brackets and collect like-terms :


5(2 - 2x) = 3x


10 - 10x = 3x


10 = 3x + 10x


10 = 13x

Second step, you have to divide it by 13 :


13x = 10


(13x)/(13) = (10)/(13)


x = (10)/(13)

User Pavel Belousov
by
5.1k points
3 votes

Answer:

10-10x=3x

10=13x

13x=10

x=10/13

User Robynne
by
5.1k points